2016
DOI: 10.4238/gmr.15027832
|View full text |Cite
|
Sign up to set email alerts
|

A replicating plasmid-based vector for GFP expression in Mycoplasma hyopneumoniae

Abstract: ABSTRACT. Mycoplasma hyopneumoniae (M. hyopneumoniae) causes porcine enzootic pneumonia (PEP) that significantly affects the pig industry worldwide. Despite the availability of the whole genome sequence, studies on the pathogenesis of this organism have been limited due to the lack of a genetic manipulation system. Therefore, the aim of the current study was to generate a general GFP reporter vector based on a replicating plasmid. Here, we describe the feasibility of GFP reporter expression in M. hyopneumoniae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Expression of GFP in M. hyopneumoniae was first reported by Ishag et al [38] who used extrachromosomal plasmid pMD18- TOgfp to express GFP. The plasmid pMD18-TOgfp possessed a gfp gene under control of the P97 gene promoter sequence, and a tetM gene under control of an additional copy of the P97 gene promoter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of GFP in M. hyopneumoniae was first reported by Ishag et al [38] who used extrachromosomal plasmid pMD18- TOgfp to express GFP. The plasmid pMD18-TOgfp possessed a gfp gene under control of the P97 gene promoter sequence, and a tetM gene under control of an additional copy of the P97 gene promoter.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to different levels of intracellular GFP in differently aged M. hyopneumoniae (pMHGFP-P97) cells. Neither Ishag et al [38] nor investigators expressing fluorescent protein in other mycoplasmas have noted a dependence of fluorescence intensity on culture time or fluorescence heterogeneity [3941]. Despite the heterogeneous nature of M. hyopneumoniae (pMHGFP-P97) fluorescence, it was still suitable to use in downstream flow cytometry and confocal microscopy experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Gene knock-ins predicted by the model could be verified when more advanced genome-editing techniques have been developed in M. hyopneumoniae. Recently, expression of GFP in M. hyopneumoniae was accomplished with a plasmid incorporating the oriC sequence and GFP expression by the P97 promoter 286 . Such a system could be applied to express a transporter for myo-inositol in M. hyopneumoniae and verify one of the gene knock-ins described in chapter 4.…”
Section: Further Improvement Of the Vaccine Production Processmentioning
confidence: 99%
“…Other than a few small plasmids (~2 kb) in species of the mycoides group (19), no plasmids have been isolated from the mycoplasmas. Plasmids with the oriC of various species have been constructed (64,65,(78)(79)(80)(81)(82)(83)(84)(85)(86)(87) and are being used for heterogenous gene expression. No transposons have been identified that are native to mycoplasmas, but Tn916 has been conjugated into M. gallisepticum (88) and M. arthritidis (46).…”
Section: Genetic Elementsmentioning
confidence: 99%